Pengaruh Service Dan Price Fairness Terhadap Costumer Satisfaction: (Studi Kasus Andalas Copy Canter) - Bintang Rifky Ramadhan Sugiarto; Pebi Kurniawan; Ali Jufri (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study analyzes the influence of service quality and price fairness on customer satisfaction at Andalas Copy Center. Based on the identified problems, namely customer dissatisfaction due to unfriendly service and relatively higher prices compared to competitors which impacts on declining sales, this study aims to determine the influence of service quality, price fairness, and both simultaneously on customer satisfaction. Using quantitative methods with data collection through questionnaire surveys and observations, the data were analyzed with data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results show that service quality and price fairness each have a simultaneous and significant positive influence on customer satisfaction at Andalas Copy Center.